Collective total synthesis of botryanes. Issue 12 (22nd March 2019) - Qiao, Chuang; Zhang, Wen; Han, Jing-Chun; Dai, Wei-Min; Li, Chuang-Chuang
Abstract: The collective total synthesis of a series of botryanes, which are an important group of sesquiterpene antibiotics isolated from the metabolites of the fungus Botrytis cinerea, has been reported. The highly functionalized hydrindane skeleton of the botryanes was efficiently synthesized via an unusual intramolecular Diels-Alder reaction, which was promoted by TsOH as a protic acid. The concise total synthesis of (±)-hypocrolide A with a challenging hexacyclic skeleton was accomplished in 8 steps from the readily available starting materials. Graphical abstract: Image 1